Role of Parliament and Governance in Bangladesh: Problems and Prospects - Hossain, Awal (Journal of Public Policy and Administration, 2023)
Purpose: This paper aims to critically evaluate the role of parliament in ensuring democratic governance as well as good governance in Bangladesh. The basic three functions of a parliament are a) law-making; b) representation; and c) oversight. Thus, parliament plays a crucial role in the development, people participation, rule of law, ensuring accountability and transparency, making laws and policies that promote good governance. Though Bangladesh has started its journey as a parliamentary form of government and past 48 years of its independence amid some(16) years of military intervention, however, the parliament of Bangladesh is not still effective to ensure the core elements of democratic or good governance by its three basic functions. Besides, the parliament of Bangladesh has been facing several problems and challenges to ensure its viability and effectiveness. The paper is a case-oriented qualitative study and based on secondary sources of materials. Methodology: The study adopted desktop literature Method Findings: The finding of this study is that a democratically elected parliament is the true voice of the people and responsible to the people which serves as the main platform of democratic governance. Besides, the quality of elections is crucial for a truly democratic parliament because parliaments can hardly fulfill their roles, specifically the role of representation, if elections are defective and controversial. Unique Contribution to Theory, Practice and Policy: The study concluded that parliament is should establish its functions through modernization by use of the latest technologies including ICT.